PEMBANGUNAN SISTEM INFORMASI PADA SD NEGERI 189 KOTA JAMBI BERBASIS WEB - Lisdarti - (JURNAL AKADEMIKA)
The writing of this manuscript describes the Analysis and Design of Information Systems at City of Edinburgh primary school 189/IV Website Based in order to assist the school in order to better convey information known by the public. This Information System using the web-based programming languages HTML, PHP, CSS and MySQL Databases relating to research obtained through field studies and literature. The conclusion by the authors in the creation of this website-based information system is the consideration for the school to assist the school to convey information efficiently to be more recognized by the public.